Legal Liability Arising from Artificial Intelligence Activities - Hussein, Al-Kayid, Jalal; Assaf, Alsalamat, Mohammad; Mansour, Aljuneidi, Fadel; Jalal , Bqoour, Karimeh (Journal of Ecohumanism, 2024)
Criminal liability concept has become widespread in light of the increasing use of artificial intelligence technologies all life aspects and it is within a wide scope that requires urgent legislative intervention. With this use of artificial intelligence, many artificial intelligence crimes have emerged in all areas of artificial intelligence in addition to problems in determining criminal liability. This study aimed to investigate artificial intelligence characteristics, clarify the legal responsibility resulting from the actions of artificial intelligence and to determine the penalty resulting from artificial intelligence actions. Results indicated that the legal responsibility resulting from the artificial intelligence actions, which has emerged at the present time after the expansion of the use of these technologies in all sectors of life is inseparable from the responsibility of the innovator, part of the factory, or all of the responsibility of each individual. Intervention in all areas of work through artificial intelligence. The study recommended with the necessity of establishing mechanisms to monitor the work that falls within artificial intelligence techniques by specialists for the purpose of avoiding technical errors that affect the safety of users of artificial intelligence technique.Artificial Intelligence